The changing role of America's veterans - Hugh Rockoff (Rutgers University, Department of Economics, 2001)
This essay provides an historical background for understanding the statistics on veterans that will appear in the millennial edition of the Historical Statistics of the United States. It describes changes in the number of veterans, and in the benefits provided by governments to veterans, from colonial times to the present. It then discusses in broad terms how political and historical forces shaped the form and amount of benefits provided to veterans, and how the programs created for veterans in turn influenced the evolution of other government programs.
Keywords: N4; 330; Veterans; Soldaten; Ruhegehalt; Geschichte; USA